DESTABILISING BELONGING: RACIAL DISCRIMINATION AND THE CONSTRUCTION OF MULTIRACIAL SUBJECTIVITY IN GINNY & GEORGIA - Deuis Sugaryamah; Agry Pramita; Ibnu Azmi Firdaus; Daniela Lacramioara Moraru; Cisya Dewantara Nugraha (CALL, 2026)
The growing visibility of multiracial characters in contemporary popular media is frequently interpreted as evidence of progressive racial inclusion. Yet increased representation does not necessarily guarantee stable identity formation within narrative structures. This study examines how racial discrimination operates as a constitutive force shaping multiracial subjectivity in the Netflix series Ginny & Georgia (2021). It employs qualitative textual analysis of eight selected scenes from Season One—chosen for their narrative significance in depicting racialised interaction, identity negotiation, and emotional responses to racial ambiguity—to examine how institutional, interpersonal, and internalised forms of racism are narratively constructed. Integrating Jones's multilevel model of racism, Du Bois's concept of double consciousness, and Turner's theory of liminality, the findings indicate that institutional positioning, interpersonal microaggressions, and internalised ambiguity collectively generate what this article conceptualises as destabilised belonging—a condition in which multiracial identity remains persistently unsettled, marked by insecurity, embodied self-harm, and relational isolation. Rather than presenting multiracial identity as harmonious hybridity, the series constructs it as an ongoing negotiation marked by fragmentation and conditional inclusion. By foregrounding the cumulative effects of subtle discrimination, the narrative challenges celebratory discourses of diversity and exposes the persistence of racial hierarchy within ostensibly inclusive environments. This study contributes to cultural and media scholarship by shifting analytical attention from representation alone to the structural and psychological consequences of discrimination in popular media narratives. It argues that multiracial visibility in streaming culture may coexist with continued instability in belonging, revealing the limits of multicultural inclusion in contemporary racial frameworks.